(untitled) (Journal of the College of Basic Education, 2022)
Was discussed this; to reveal aspects of proportionality between the acoustic structure in the Holy Quran and meanings.We opted blessed Gash, to be room for the application, Divided our study them to two sections, Opened boot Summary knew which Surat Gash, then was the first topic (Sign language sounds in terms of output and capacity),We connect the sounds and exits characteristics in terms of speaking out and whisper, laxity and intensity and arrogance and decline, and so in terms of words in context. The other topic handled (rhythm performance Altjoada and significant), as spotted by some provisions Altjoadah in rulings Noon Gash static and special characters, and the provisions of the tide,Revealing what arises from the commitment of those rules of the impact of my voice feels sense